Pollen Collection and Brood Production by Honeybees (Apis mellifera L.) under Chitwan Condition of Nepal - Neupane, KR; Thapa, RB (Journal of the Institute of Agriculture and Animal Science, 2005)
A study was carried out to investigate pollen foraging, storage and its impact on Apis mellifera L brood production throughout the year under Terai condition of Nepal in 2003-2005. Number of pollen foragers, amount of pollen stored as beebread and brood in the colony differed significantly during different seasons. Number of pollen foragers (117.5 bees/ hive/ 5 min) and amount of pollen as beebread (2439.0 gm/hive) and number of brood (14787.2 brood cells/hive) were the highest during spring season, while the lowest number of pollen foragers (38.1 bees/ hive/5 min.) stored the lowest amount of beebread or pollen store (152.5 gm /hive) and produced the lowest number of brood (3811.7 brood cells/ hive) and bees in rainy season. Autumn, winter and summer seasons were normal for pollen collection and brood production, while starvation and nutritional deficiencies due to the acute shortage of pollen in rainy season was the major reason to decline or collapse the bee population before the honey flow season. Therefore, feeding bees with adequate amount of nutritionally rich pollen during rainy season is essential to maintain a healthy and strong bee colony for the production of higher honey and other hive products. Key words: Honeybees, foraging, pollen, brood, Apis mellifera J. Inst. Agric. Anim. Sci. 26: 143-148 (2005)